Becoming a mother entails anatomical changes in the ventral striatum of the human brain that facilitate its responsiveness to offspring cues. (February 2020) - Hoekzema, Elseline; Tamnes, Christian K.; Berns, Puck; Barba-Müller, Erika; Pozzobon, Cristina; Picado, Marisol; Lucco, Florencio; Martínez-García, Magdalena; Desco, Manuel; Ballesteros, Agustín; Crone, Eveline A.; Vilarroya, Oscar; et al.
Highlights: Pregnancy renders anatomical reductions in the human ventral striatum (VStr). VStr decreases are associated with stronger responses to offspring cues in the VStr. Pregnancy may adaptively tune the reward circuit to promote offspring responsivity. Abstract: In mothers, offspring cues are associated with a powerful reinforcing value that motivates maternal care. Animal studies show that this is mediated by dopamine release into the nucleus accumbens, a core component of the brain's reward system located in the ventral striatum (VStr). The VStr is also known to respond to infant signals in human mothers. However, it is unknown whether pregnancy modifies the anatomy or functionality of this structure, and whether such modifications underlie its strong reactivity to offspring cues. Therefore, we analyzed structural and functional neuroimaging data from a unique pre-conception prospective cohort study involving first-time mothers investigated before and after their pregnancy as well as nulliparous control women scanned at similar time intervals. First, we delineated the anatomy of the VStr in each subject's neuroanatomical space and examined whether there are volumetric changes in this structure across sessions. Then, we tested if these changes could predict the mothers' brain responses to visual stimuli of their infants. We found decreases in the right VStr and a trend for left VStr reductions in the women who were pregnant between sessions compared to the women who were not. Furthermore, VStr volume reductions across pregnancy were associated with infant-related VStr responses in the postpartum period, with stronger volume decreases predicting stronger functional activation to offspring cues. These findings provide the first indications that the transition to motherhood renders anatomical adaptations in the VStr that promote the strong responsiveness of a mother's reward circuit to cues of her infant.